Nuclear resonance vibrational spectroscopy and electron paramagnetic resonance spectroscopy of 57Fe-enriched [FeFe] hydrogenase indicate stepwise assembly of the H-cluster. - Kuchenreuther, J; Guo, Y; Wang, H; Myers, W; George, S; Boyke, C; Yoda, Y; Alp, E; Zhao, J; Britt, R; Swartz, JR; Cramer, S (2013)
The [FeFe] hydrogenase from Clostridium pasteurianum (CpI) harbors four Fe-S clusters that facilitate the transfer of an electron to the H-cluster, a ligand-coordinated six-iron prosthetic group that catalyzes the redox interconversion of protons and H(2). Here, we have used (57)Fe nuclear resonance vibrational spectroscopy (NRVS) to study the iron centers in CpI, and we compare our data to that for a [4Fe-4S] ferredoxin as well as a model complex resembling the [2Fe](H) catalytic domain of the H-cluster. To enrich the hydrogenase with (57)Fe nuclei, we used cell-free methods to post-translationally mature the enzyme. Specifically, inactive CpI apoprotein with (56)Fe-labeled Fe-S clusters was activated in vitro using (57)Fe-enriched maturation proteins. This approach enabled us to selectively label the [2Fe](H) subcluster with (57)Fe, which NRVS confirms by detecting (57)Fe-CO and (57)Fe-CN normal modes from the H-cluster nonprotein ligands. The NRVS and iron quantification results also suggest that the hydrogenase contains a second (57)Fe-S cluster. Electron paramagnetic resonance (EPR) spectroscopy indicates that this (57)Fe-enriched metal center is not the [4Fe-4S](H) subcluster of the H-cluster. This finding demonstrates that the CpI hydrogenase retained an (56)Fe-enriched [4Fe-4S](H) cluster during in vitro maturation, providing unambiguous evidence of stepwise assembly of the H-cluster. In addition, this work represents the first NRVS characterization of [FeFe] hydrogenases.